THE ROLE OF ARCHAEOLOGICAL TOURISM IN THE FORMATION OF HISTORICAL CITIES OF THE FERGHANA REGION - Muminova , Nigoraxon Zokhidovna (Educational Research in Universal Sciences, 2024)
This article discusses the role, problems and proposals for the development of archeological tourism in the formation and development of historical cities in Fergana region.